2015
DOI: 10.1063/1.4927816
|View full text |Cite
|
Sign up to set email alerts
|

Li transport in fresh and aged LiMn2O4 cathodes via electrochemical strain microscopy

Abstract: Transport properties of Li þ mobile ions in fresh and aged LiMn 2 O 4 battery cathodes were studied at the nanoscale via electrochemical strain microscopy (ESM), time spectroscopy, and voltage spectroscopy mapping. Both Vegard and plausible non-Vegard contributions to the ESM signal were identified in electrochemical hysteresis loops obtained on fresh and aged samples. In the fresh cathodes, the Vegard contribution dominates the signal, while in the aged samples different shape of hysteresis loops indicates an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 38 publications
0
44
0
Order By: Relevance
“…9(d). In this case, because the hysteresis loop area represents the degree of redistribution of lithium ions and is directly proportional to the magnitude of the electrochemical strain, [106,107] it is inferred that the large hysteresis loop can be obtained from the strong redistribution of lithium ions. Whereas the hysteresis loop with a small area does not show clear hysteric behavior, the large loop indicates ferroelectric-like hysteric behavior.…”
Section: Electrochemical Strainmentioning
confidence: 99%
“…9(d). In this case, because the hysteresis loop area represents the degree of redistribution of lithium ions and is directly proportional to the magnitude of the electrochemical strain, [106,107] it is inferred that the large hysteresis loop can be obtained from the strong redistribution of lithium ions. Whereas the hysteresis loop with a small area does not show clear hysteric behavior, the large loop indicates ferroelectric-like hysteric behavior.…”
Section: Electrochemical Strainmentioning
confidence: 99%
“…248,257 The original description of ESM mechanism considered purely diffusional dynamics with fast voltage controlled generation-recombination of ionic species on the surface and near surface regions. 258 Subsequently, the model was extended to include both migration transport [259][260][261] and electrostrictive effects. 118,262,263 Finally, it was shown that ESM mechanism can be present even in the absence of a surface reaction.…”
Section: B Electrochemical Strain Microscopy (Esm)mentioning
confidence: 99%
“…5 At the same time, ESM experiments on commercial Li-ion battery electrodes comprising the particles of ionic conductors embedded in a polymer binder matrix represent non-trivial problem due to complex geometry of the samples 6 and consequent difficulties 7 resulting in less predictable contributions of different origin into the strain response. 8,9 From that point of view, we can generally talk about strain-based SPM (s-SPM) with a number of contributions, which must be separated in the experiments. 10 Understanding and separation of these contributions is an important step from purely qualitative to quantitative data interpretation and analysis.…”
mentioning
confidence: 99%